KOMBINASI MCKENZIE EXERCISE DAN ULTRASOUND LEBIH BAIK DARIPADA MYOFASCIAL RELEASE DAN ULTRASOUND UNTUK MEMPERBAIKI DISABILITAS PADA MECHANICAL NECK PAIN - Jasmine Kartiko Pertiwi; Ketut Tirtayasa; Sugijanto -; J. Alex. Pangkahila; I Made Muliarta; S. Indra Lesmana (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2017)
Introdaction: Patients with mechanic neck pain a population that often found overstretches it is caused by occurred between the two bones in the neck on the ligaments and soft tissues located around, static resulting in hipomibilitas the joint space and joint play movement, resulting in the emergence of provocation on the part of the occipital region on Cervical stressor resulting in excess tissue around the contractile and non-contractile. Purpose: This study the application of ultrasound and McKenzie exercise and myofacial release ultrasound in reducing disability in mechanical neck pain, Methods: This research method is a quasi experimental research with Pre and Post Test Two Group Design. The samples were divided into two treatment groups consisting of McKenzie exercice and ultrasounds were 20 participants with myofascial release and ultrasound with 19 participants, a total of 39 participants. Result: Differences between the mean decrease in neck with NDI disability before and after the application of each group were tested by t-test related, the results obtained mean between the groups before treatment 17,10±1,889% and after treatment 12,90±2,490% by value (p = 0.001) with a mean difference of 42% and showed the average group between before treatment 17,42±2,388% and after treatment 15,63±2,362% (p = 0.001) with a mean difference of 17,9%. The statistical test of using independent t-test showed is a significant difference between group I and group II and the result is p = 0.001 (p< 0.05). Conclusion: application of combined Mc Kenzie exercise and ultrasound better than the application of a combination of myofacial release and ultrasound in reducing disabilities in case of mechanical neck pain.